Seismic Reduction Performance of Wrap Rope Connection Devices for Continuous Girder Bridges - Yanfang Liu; Wenxue Zhang; Xiuli Du; Weigang Bao (Advances in Civil Engineering)
In this article, wrap rope connection device (WRCD), which considers the relative acceleration of piers and beam as a control variable, is proposed for improving the current situation of continuous girder bridges whose bearing force of a single pier is along the longitudinal direction and based on the synergy principle. The WRCD device, which meets the slow displacement requirements of temperature and vehicle load under normal operation, is implemented and used to improve the performance of the sliding bearing pier. During earthquakes, because of the amplification effect of the wrap rope, the instantaneous large stiffness state in the longitudinal force can be achieved. Based on the shaking table test of a typical continuous girder bridge for examining the performance of the WRCD during earthquakes, the dynamic characteristics, structural acceleration, displacement, and strain responses of the structure under different frequency spectra, and seismic input intensities are analyzed and the seismic reduction performance of the WRCD is demonstrated. This analysis demonstrated that, by activating WRCD, the ratio of the acceleration response of the fixed bearing pier to the sliding bearing pier increased from 10% to 57%; moreover, the force on each pier appeared more uniform. Furthermore, with an increase in the input intensity of the earthquake, the displacement of the primary beam and the seismic response of the fixed pier bottom considerably decreased and the synergy effect of each pier was more prominent. Under certain site conditions, the WRCD can effectively improve the synergy effect between the sliding bearing piers and fixed bearing pier; however, the improvement in the obtained result is directly associated with the seismic input characteristics. The design parameters of the WRCD should be determined as per different site conditions and the optimum application range of the WRCD.